In vitro antiproliferative activity of ethanolic extract of Sida cordifolia Linn against various cancer cell lines - Pratima M. Bhutkar; V. Suganthi; Milind V. Bhutkar; R. Kothai (Al Ameen Medical College, 2020)
Background: Sida cordifolia of family Malvaceae is traditionally, used in treating the various ailments of respiratory and urinary system. It possesses astringent and emollient properties. Aim and objectives: Present study was aimed to assess in vitro antioxidant and antiproliferative potential of aerial parts of Sida cordifolia. Material and Methods: Serial extraction of aerial parts of Sida cordifolia was done by using Soxhlet apparatus. In vitro antioxidant potential was evaluated by DPPH, H2O2 and NO radical scavenging ability. Antiproliferative activity was assessed by MTT assay on human breast cancer (MCF7), ovarian cancer (PA1), colon cancer (HT29), melanoma (A375), liver cancer (HepG2) and normal mouse embryonic fibroblast (NIH-3T3) cell lines by treating them with increasing concentration of the extract for 24 hours. Results: Ethanolic extract of S. cordifolia showed good DPPH, H2O2 and NO radical scavenging activity (IC50 value 20.93µg/mL, 85.14μg/mL and 320.99µg/mL respectively). Extract also showed dose dependent cytotoxicity against all cancer cell lines used in the study. Among cancer cell lines, A375 and HT29 were more sensitive (IC50 16.51 and 49.86μg/mL respectively) than the other cancer cell lines. Conclusion: Further work to study mechanism of its action on these cell lines can be helpful in drug discovery program.